2021
DOI: 10.3389/fcell.2020.631460
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Fungal Dysbiosis in Chinese Patients With Alzheimer’s Disease

Abstract: Gut bacterial dysbiosis plays a vital role in the development of Alzheimer’s disease (AD). However, our understanding of alterations to the gut fungal microbiota and their correlations with host immunity in AD is still limited. Samples were obtained from 88 Chinese patients with AD, and 65 age- and gender-matched, cognitively normal controls. Using these samples, we investigated the fungal microbiota targeting internal transcribed spacer 2 (ITS2) rRNA genes using MiSeq sequencing, and analyzed their associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 72 publications
1
40
0
Order By: Relevance
“…Gut microbiota is involved in important homeostatic processes, not only related to gastrointestinal function but also to several complex modulatory processes, such as glucose and bone metabolism, inflammation and immune response, and peripheral (enteric), and central neurotransmission (De-Paula et al, 2018). Growing evidence has revealed that gut microbiota participates actively in the development of obesity, diabetes, cancers, aging, autoimmune diseases and even neuropsychiatric disorders such as depression and AD (Jiang et al, 2015;Zhang et al, 2015;Cattaneo et al, 2017;Zhao et al, 2018;Li B. et al, 2019;Ling et al, 2019Ling et al, , 2021aLiu X. et al, 2019;Liu X. et al, 2020;Cheng et al, 2020;Sun et al, 2021). As mentioned by Cani, gut microbiota may be "at the intersection of everything, " being implicated in virtually all physiological or pathological situations (Cani, 2017).…”
Section: Alterations In Gut Microbiota In Patients With Admentioning
confidence: 99%
See 1 more Smart Citation
“…Gut microbiota is involved in important homeostatic processes, not only related to gastrointestinal function but also to several complex modulatory processes, such as glucose and bone metabolism, inflammation and immune response, and peripheral (enteric), and central neurotransmission (De-Paula et al, 2018). Growing evidence has revealed that gut microbiota participates actively in the development of obesity, diabetes, cancers, aging, autoimmune diseases and even neuropsychiatric disorders such as depression and AD (Jiang et al, 2015;Zhang et al, 2015;Cattaneo et al, 2017;Zhao et al, 2018;Li B. et al, 2019;Ling et al, 2019Ling et al, , 2021aLiu X. et al, 2019;Liu X. et al, 2020;Cheng et al, 2020;Sun et al, 2021). As mentioned by Cani, gut microbiota may be "at the intersection of everything, " being implicated in virtually all physiological or pathological situations (Cani, 2017).…”
Section: Alterations In Gut Microbiota In Patients With Admentioning
confidence: 99%
“…Similar to Li's findings (Li B. et al, 2019), this study also found that functional dysbiosis, especially the microbial gene functions related to metabolism and biosynthesis of fatty acids, are overactivated in the gut microbiota of patients with AD. Recently, we also explored the alterations in the fungal microbiota in Chinese patients with AD for the first time (Ling et al, 2021a). Fungi are suggested to influence intestinal health and disease by suppressing the outgrowth of potential pathogens, promoting immunoregulatory pathways, and modulating host metabolism (Huseyin et al, 2017;Ni et al, 2017;Sam et al, 2017;Chin et al, 2020).…”
Section: Alterations In Gut Microbiota In Patients With Admentioning
confidence: 99%
“…Retinol hypofunction and impaired transport may contribute to patients with memory impairment in Alzheimer’s disease (AD) and dementia ( Goodman and Pardee, 2003 ). Two metabolic pathways, pentose and glucuronate interconversions ( Zheng et al, 2019 ), and starch and sucrose metabolism ( Ling et al, 2021 ) may play roles in learning and cognitive impairment that are caused by abnormal nitric oxide production and monoaminergic neurotransmitters in AD, BPD, and/or dementia patients. Other metabolisms, including porphyrin and chlorophyll metabolism ( Wang et al, 2015 ), and ascorbate and aldarate metabolism ( Chen et al, 2011 ) were biologically or molecularly connected with psychiatric disorders (e.g., AD, BPD) and dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that gut microbiota is altered in AD. When AD patients were compared with healthy controls, AD patients exhibited diverse microbiota, an increased abundance of Bacteroidetes , and a reduced abundance of Firmicutes , Proteobacteria , and Actinobacteria ( 88 , 89 ). Moreover, the composition of the gut microbiota of SAPM8 mice, which exhibited learning and cognitive impairment similar to AD patients, revealed conspicuous character divergence compared with that of the healthy control; the correlation density and clustering operational taxonomic unit of gut microbiota decreased ( 87 ).…”
Section: From Bench To Clinic: the Emerging Role Of Gut Microbiota In...mentioning
confidence: 99%